Agile flight control under multiple disturbances for quadrotor: algorithms and evaluation - Jia, Jindou (2022)
In this article, a scheme of anti-disturbance agile flight control is developed for a maneuverable quadrotor unmanned aerial vehicle, subject to the aerodynamic drag, dynamic shift of center of gravity (CoG), and motor dynamics. A cascaded control framework is adopted. In the translational loop, an aerodynamic drag model that considers the drag surface change is developed, containing the deep coupling information between the aerodynamic drag and the system states. A disturbance observer based on the aerodynamic drag model is subsequently designed for suppressing the aerodynamic drag force. In the rotational loop, a full quaternion-based backstepping control is adopted and a nonlinear disturbance observer with consideration of motor dynamics is designed, which can handle the dynamic CoG shift and aerodynamic drag torque. Comparative studies on both simulations and experiments manifest that the agile ability can be ensured by the proposed control framework, especially in the presence of multiple disturbances.